Ferroportin depletes iron needed for cell cycle progression in head and neck squamous cell carcinoma - Belvin, Benjamin Ross; Lewis, Janina P. (Frontiers in Oncology, 2023)
Ferroportin (FPN), the only identified eukaryotic iron efflux channel, plays an important role in iron homeostasis and is down regulated in many cancers. To determine if iron related pathways are important for and neck squamous cell carcinoma (HNSCC) progression and proliferation, we overexpress FPN to simulate iron depletion and probe associated molecular pathways. HNSCC cells are sensitive to iron chelation and ferroptosis, but a non-transformed normal oral keratinocyte (NOK) cell line is not. We found that FPN expression inhibits HNSCC cell proliferation and colony formation but NOK cells are unaffected. Inhibition of cell proliferation are due to the disruption of iron homeostasis via loss of labile iron caused by elevated FPN levels and that phenotype can be is rescued by the addition hepcidin that marks FPN for proteolytic degradation. We show that expression of FPN induces DNA damage, activates p21 and reduces mRNA levels of cyclin proteins thereby inhibiting cell cycle progression of HNSCC cells, arresting cells in S-phase. Induction of FPN severely inhibits Edu incorporation and increases β-galactosidase activity, indicating cells have entered senescence. Finally, in an oral orthotopic mouse xenograft model, FPN induction yields a decrease of tumor growth. Our results indicate that iron plays a role in HNSCC cell proliferation and sustained growth and ferroptosis iron based therapeutic strategies may have potential therapeutic benefit.